(untitled) - Louw, Eugenie-Lien (nee Bezuidenhout)

Growth manipulations of Leucospermum cut flowers with the application of plant growth regulators (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDAgric)--Stellenbosch University, 2020.